Étude et restauration d’une empreinte et contre-empreinte d’Urolophus crassicaudatus - Aline Raux (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The fossil prints of Urolophus crassicaudatus, seized by Napoleon Bonaparte during the first campaign of Italy, are since conserved at the National History Museum of Paris. Our study of the former fossils’ preparation, previously little documented, proved essential to discern the former materials from more recent additions and able us to realize a significant work of de-restoration.